Konsumsi Energi Protokol Routing Zone Routing Protocol (ZRP) Pada Mobile Ad-Hoc Network (MANET) - Faiz Amzadkhan Fajar; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Mobile Ad-Hoc Network (MANET) is a network technology formed from connected device without depending on fixed-network infrastructure. The nodes in MANET are dynamic, they can freely move at varying speed. Besides, nodes also have multifunctional roles, which can be a sender, receiver, or an agent. Accordingly, one of the major issues in MANET is consumption of the energy. In this research, Zone Routing Protocol (ZRP) implemented on Mobile Ad-Hoc Network. The simulation applied on Network Simulator 2 (NS2) with Fixed Grid and Random Waypoint as a mobility model, also with various number of nodes (30,50,70). It is carried out in 1000 m x 1000 m simulation area for Random Waypoint mobility with 2 m/s - 5 m/s nodes speed. The result showed that average of the energy consumption for Fixed Grid mobility 30 nodes is 774.822 Joules, average of the energy consumption for Fixed Grid mobility 50 nodes is 801.931 Joules, and 882.064 Joules for Fixed Grid mobility 70 nodes. The average energy consumption on Random Waypoint mobility for 30 nodes is 900.626 Joules, 50 nodes is 880.784 Joules, and 772.889 Joules for 70 nodes. Based on the result, it can be concluded that average of the energy consumption for Fixed Grid mobility is increase along with increasing number of nodes. However, average of the energy consumption for Random Waypoint is decrease along with increasing number of nodes.